Analisis Rekrutmen Beban Kerja Pendidik dan Tenaga Kependidikan di MTs. Bina Insani - Khoiriyah, Yuni Siti; Salma, Masyqi; Merduani, Frestinata Arum; Trihantoyo, Syunu; Wulandari, Ayu (Al-DYAS, 2023)
Analysis of the recruitment and workload of educators and education staff at Mts. Human Development. With the focus of his research on recruitment and workload based on an analysis of the workload carried out by educators and education staff at Mts.Bina Insani. The purpose of this study is to determine the recruitment and fulfillment of the workload of educators and education staff at Mts. Bina Insani, this research method is a descriptive research with a qualitative approach with data collection techniques carried out by observation and documentation. While the data analysis technique uses the data reduction stage, data presentation and drawing conclusions. The results of the study show that educators and education staff at Mts. Bina Insani has carried out the duties and responsibilities according to the workload.